Tinnitus Assessment and Management: A Survey of Practicing Audiologists in the United States and Canada - Sheppard, Adam; Ishida, Ieda; Holder, Thea; Stocking, Christina; Qian, Jinyu; Sun, Wei (Journal of the American Academy of Audiology, 2022)
Background Tinnitus is a prevalent auditory disorder that can become severely debilitating. Despite decades of investigation, there remains no conclusive cure for tinnitus. Clinical practice guidelines (CPGs) are available for assessing and managing tinnitus. Even though such guidelines have been available for several years, the degree that audiologists adhere to them has remained unexplored.Purpose of Study To determine what clinical practices are commonly used by audiologists in the assessment and management of the patient population with tinnitus, we administered an online survey to audiologists practicing in the United States and Canada.Results Among the audiologists that completed the survey and were included in the final analysis (n = 61), 70% were from the United States and 30% were from Canada. The audiologists represented a wide range of clinical experience (1–35 years). On average, those who completed the survey were relatively confident in their ability to assess and manage tinnitus patients indicated by a 0 to 100 Likert scale, with 0 representing no confidence (mean 72.5, ± 21.5 standard deviation). The most commonly reported tinnitus assessment tools were pure tone audiogram (0.25–8 kHz), administration of standardized questionnaires, and tinnitus pitch and loudness matching. Approximately half (55%) of audiologists indicated they include otoacoustic emissions, while less audiologists (<40%) reported measuring high-frequency thresholds, minimum masking levels, or loudness discomfort levels. The most common recommendation for tinnitus patients was amplification (87%), followed by counseling (80%) and sound therapy (79%).Conclusion Few audiologists administer a truly comprehensive tinnitus assessment and ∼20% indicated not recommending counseling or sound therapy to manage tinnitus. The results are discussed in the context of what is explicitly indicated in published CPGs, professional organization recommendations, and recent findings of peer-reviewed literature.
Keywords: tinnitus assessment; tinnitus management